0962 Adverse Childhood Experiences Among Student Athletes Are Associated with Sleep Disturbances: Evaluating the Mediating Roles of Depression and Anxiety. (27th April 2018) - Barnard, S; Athey, A; Killgore, W D; Alfonso-Miller, P; Grandner, M A
Abstract: Introduction: Experiencing traumatic life events in childhood has previously been found to increase the likelihood of health-risk behavior, leading to poor physical health in adulthood. Student athletes are a group at risk for poor sleep, as well as adverse childhood experiences (ACEs). The present study examined the relationship between ACEs in student athletes with the experience of poor sleep, and the role of depression/anxiety. Methods: Survey data from N=189 NCAA Division-I student-athletes were collected. Sleep assessments included insomnia (Insomnia Severity Index [ISI]), sleep quality (Pittsburgh Sleep Quality Index [PSQI]), fatigue (Fatigue Severity Scale [FSS]), and sleep duration (item from the PSQI). The following ACEs were assessed: verbal abuse, physical abuse, sexual abuse, feeling alone, neglect, living with addict, living with mentally ill, and loss of parent. Regression analyses examined ACEs total score, adjusted for age and sex, in predicting insomnia, poor sleep quality, sleep duration, and fatigue scores. Post-hoc analyses examined whether these relationships were mediated by depression (CESD) and/or anxiety (GAD7), and whether specific ACEs were more related to sleep than others. Results: ACES score was associated with worse insomnia (B=0.7, 95%CI[0.4, 1.5], p=0.039) and sleep quality (B=0.7, 95%CI[0.2, 1.1], p=0.003) and less sleep (B=-14.0, 95%CI[-23.5, -4.4], p=0.004), but not greater fatigue. Results were mediated by mental health for all outcomes except sleep duration. "Feeling alone" was the ACE that demonstrated the strongest individual relationships with sleep outcomes. Conclusion: Child exposures to trauma are associated with sleep disturbances in early adulthood, especially feeling alone. These relationships are largely accounted for by depression/anxiety, except for shortened sleep duration. Support (If Any): NCAA Innovations Grant.